Phytochemical And Pharmacological Evaluation Of Hydroalcoholic Extract Of Amaranthus Viridis Linn (Journal of Pharmaceutical Negative Results, 2022)
Infectious disease are the major cause of morbidity and mortality and thus a serious public health problem in developing countries. Despite the arsenal of antibiotics available, the situation is worsening due to emerging drug resistance. Antimicrobial resistance is a major issue these days due to extensive use or misuse of antibiotics. Hence, there is an urgent need to find some new interventions. Amaranthus viridis Linn (Family: Amaranthaceae) is commonly known as“chowlai”is acommonwild vegetable andiswidely grow in gunderawi derange of climatic conditions and has been utilizedasa medicin alherbin traditional ayurvedic medicine for the treatment of inflammation, diabetic, asthma, leprosy, cancer etc. Amaranthus viridis Linnincludes various biologicallyactive constituents such as saponin, tannin, phenols, flavonoids, alkaloids, cardiac glycosides,steroid and triterpenoids. This,medicinalplantsis a sourceformanypharmaceutical drugs and indicated in many infections and diseases.The design of this study was to evaluate the preliminary phytochemical contents and toanalyse thephytocompounds present in the hydroalcoholic leaf extract of Amaranthus viridisLinnby using Liquid chromatography - Mass spectroscopy (LC-MS) and in-vitro evaluationsare need edto exploreagains tpatho genicmicroorganism. Preparation of Amaranthus viridis Linn. Leaves extract using ethanol and water (80:20), followed by preliminary phytochemical screening of the extract, estimation of phenolic content and mass determination with LCMS, and evaluation of in vitro Antibacterial, Antifungal and Anthelmintic activity. Based on the findings of our studies, we conclude that hydro alcoholic extract of Amaranthus viridis Linn has potent anthelmintic, antifungal and antibiotic activity attributed to the presence of an secondary metabolite flavonoids (quercetin).It was confirmed by analyzing the phytocompounds by LC-MS and compared with total phenolic content identified by UV Visible spectroscopy shows that highest amount of flavonoids (quercetin) present in the Hydroalcoholic extract of Amaranthus viridis Linn. However, further studies need to be carried out to investigate the molecular mechanism of the secondary metabolite.